Pre-applied mechanically bonded waterproofing membranes: Cement paste filtration process and influencing parameters. (15th December 2022) - Heinlein, Ulli; Freimann, Thomas
Abstract: Pre-applied bonded waterproofing membranes are used as positive-side waterproofing on the exterior of concrete basements. They are installed on a formwork before reinforcement works and bind to the subsequently placed fresh concrete. This bond is often ensured via nonwovens as they are filled with cement paste during the concrete placement. However, it is largely unclear how the cement paste enters the nonwoven, what its properties are and how it is affected by site-specific influences and nonwoven properties. The work presented in this article used a new test stand and exposed varying nonwovens to concrete pouring conditions similar to the construction site and analyzed the filtrated cement paste. In combination with existing literature, a working model of the processes within the nonwovens was then created: After the fresh concrete is poured, a limited mass of solids and water is separated due to the mere static load, resulting in a water-rich paste within the nonwoven after a few minutes. Simultaneously, a filter cake forms on top of the nonwoven, limiting the further separation of solids. Subsequent vibration compaction loosens the filter cake, carrying more solids into the nonwoven and reducing the water/solid-ratio of the paste. The separated solid mass depends on the pore volume of the nonwoven, compaction time, and fresh concrete spread. The particle size varies over time and position in the nonwoven. Highlights: Ten nonwovens were used to investigate the cement paste filtration process. A hypothesis was made on how cement paste is separated and enters a nonwoven. During concrete placement, a filter cake builds up, determining solid separation. The water/solid ratio within the nonwoven is higher than in the fresh concrete. Thin nonwovens and high vibration compaction energies ensure a waterproof bond.